Assessing demand, efficiency and impact of tourism industry in Malaysia - Muhammad Hanif bin Othman (Kulliyyah of Economics & Management Sciences, International Islamic University Malaysia, 2019)
Tourism is an important economic sector for most countries, and it is also one of the world‟s fastest growing industries. The increasing importance of tourism in boosting national economies such as Malaysia has sparked considerable interest to better understand the entire tourism ecosystem for greater sustainability. This thesis comprises three essays on the tourism industry in Malaysia. The essays are empirical investigations on various perspectives of tourism system. The first essay explores the generating aspect of the tourism system to identify the macroeconomic demand factors and their relative importance. The second essay explores the tourism sector from the perspective of efficiency and productivity. The last essay examines the impact of homestay programme using a case study in Sepang, Selangor. Overall, the interconnection between the findings of the three essays suggests that various measures are pertinent to the theme of sustainable tourism ecosystem from the perspective of policy makers. Findings from first essay suggest that Malaysia has greater potential to attract tourist arrivals from the neighbouring countries as well as Muslim countries. Despite the great potentials that exist, the finding from the second essay suggests that there are variations in the level of efficiencies between states. These variations imply that resources are not being fully utilized or there are excessive of inputs that duplicate one another. Notwithstanding these issues, findings from last essay which is based on a case study suggests that better utilization of tourism resources could bring positive spillover effects to the surrounding communities.